Microbiological quality and allergen assessment of vegan-labelled foods sold in Turin - Sara Morello; Carla Ferraris; Clara Tramuta; Alessandra Provera; Samantha Lupi; Aitor Garcia-Vozmediano; Cristiana Maurella; Daniela Manila Bianchi (Journal of Consumer Protection and Food Safety, 2026)
The consumption of vegan-labelled foods has increased due to ethical, environmental, and health motivations, yet comprehensive evaluations of their microbiological safety and undeclared animal-derived allergens remain limited. This study analyzed 34 vegan products from Turin, Italy, using microbiological assays alongside biomolecular and immunoenzymatic techniques to detect crustacean and vertebrate DNA, as well as milk and egg proteins. Results showed no presence of Salmonella spp ., Listeria monocytogenes , milk, egg, or crustacean allergens; Enterobacteriaceae were detected within acceptable limits in 2 samples, and vertebrate DNA was found in one non-dairy cheese alternative. Overall, these findings indicate generally good hygienic quality and effective allergen management in the analysed products. These results provide baseline evidence to support future risk assessments and regulatory considerations in the plant-based food sector.